2022
DOI: 10.1186/s12889-022-13141-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the protective behavioral intentions for parents with young children that possess different levels of education in Hong Kong using the theory of planned behavior for air polluted with PM2.5

Abstract: Background Air pollution has fast become an issue with great environmental and human health problems that can be attributed to rapid global industrialization and urbanization that has strong negative impacts on human health. Children are particularly vulnerable. While studies on the effects and toxicology of particulate matter pollutants that are 2.5 microns or smaller in size (PM2.5) are abundant, understanding the factors that influence human behaviors against or the avoidance of exposure/con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Parents with an undergraduate level education exhibited no significant route from AT to PBC, and also no significant route from to BI, while the parents with postgraduate education demonstrated a statistically significant route from AT to PBC and SN to BI. However, both parents with postgraduate and those with undergraduate attainment showed no significant route from AT to BI [4].…”
Section: Limitationsmentioning
confidence: 82%
See 2 more Smart Citations
“…Parents with an undergraduate level education exhibited no significant route from AT to PBC, and also no significant route from to BI, while the parents with postgraduate education demonstrated a statistically significant route from AT to PBC and SN to BI. However, both parents with postgraduate and those with undergraduate attainment showed no significant route from AT to BI [4].…”
Section: Limitationsmentioning
confidence: 82%
“…Economics, age, and sex are factors that affect prevention behavior. Liu et al [3] and Woo [4] determined education as a key factor. In that study, behavior intentions were found between parents with postgraduate-level education and those with undergraduate education only.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology has been applied to hundreds of medical, sociological, environmental, and marketing studies that use non-probabilistic convenience sampling surveys such as questionnaires to analyse the responses from different populations or groups [ 1 , 97 , 98 ]. We explored whether IR could meet the needs of the public using the TPB using the responses from the two populations.…”
Section: Methodsmentioning
confidence: 99%